Effect of garlic (Allium sativum) extract on the growth and disease resistance of Carassius auratus(Linneaus, 1758) - Sasmal, Debasis; Babu, Ch. Surendra; Abraham, T Jawahar (Indian Journal of Fisheries, 2011)
Effect of garlic (Allium sativum) extract on the growth and disease resistance of Carassius auratus(Linneaus, 1758)